1983
DOI: 10.3109/03005368309081485
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Studies of Tinnitus Masking and Residual Inhibition

Abstract: A study was made of the relation between tinnitus masker composition (frequency, bandwidth, intensity duration) and the time course and magnitude of residual inhibition (RI). RI was determined by methods of (a) loudness estimation - where the subject varied the pointer position on a loudness scale (b) loudness balance - where the tinnitus loudness was maintained in loudness balance in the period following masking with a tone of variable intensity presented to the opposite ear. In addition, sensitivity change (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 13 publications
3
63
0
Order By: Relevance
“…The difference might be explained by the masker duration. Residual inhibition has been demonstrated to be related to the logarithm of the masker duration, for masker duration of 10 seconds to 10 minutes 19 . Our observed correlation between MML and residual inhibition is similar to observations of previous studies 20,21 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The difference might be explained by the masker duration. Residual inhibition has been demonstrated to be related to the logarithm of the masker duration, for masker duration of 10 seconds to 10 minutes 19 . Our observed correlation between MML and residual inhibition is similar to observations of previous studies 20,21 .…”
Section: Discussionmentioning
confidence: 98%
“…Terry et al 19 observed that contralateral masking did not produce residual inhibition. We however obtained residual inhibition ranging from 2 to 50 seconds in participants with bilateral tinnitus when the worse ear was exposed to MML + 10 broad band sound for 60 seconds.…”
Section: Discussionmentioning
confidence: 98%
“…Second, the defining effect is different-a loudness reduction in one case and a threshold elevation in the other. Third, the temporal pattern of effect is different: Tinnitus can be masked for several minutes or even hours after a masking sound is turned off (i.e., residual inhibition, see Feldmann 1971;Terry et al 1983) but sound audibility is hardly affected beyond a hundred milliseconds (e.g., Jesteadt et al 1982). Here, we use the "tinnitus masking" definition to compare the present study with previous studies.…”
Section: Comparison With Previous Studiesmentioning
confidence: 92%
“…While this method is effective in eliminating the tinnitus percept for the duration of the noise, it is seldom adopted by patients, as it accomplishes little more than replacing one auditory annoyance by another. Interestingly, a residual inhibition following the masking noise and lasting up to minutes is commonly observed 68 . It has also been reported that hearing aids properly fitted to the frequencies of hearing loss can sometimes alleviate tinnitus 3,69,70 .…”
Section: A Evidence Related To Tinnitus and Hearing Lossmentioning
confidence: 99%